Recombinant BCG-LTAK63 Vaccine Candidate for Tuberculosis Induces an Inflammatory Profile in Human Macrophages - Dos Santos, Carina C; Walburg, Kimberley V; van Veen, Suzanne; Wilson, Louis G; Trufen, Carlos E M; Nascimento, Ivan P; Ottenhoff, Tom H M; Leite, Luciana C C; Haks, Mariëlle C (Vaccines, 2022)
Tuberculosis (TB) is one of the top 10 leading causes of death worldwide. The recombinant BCG strain expressing the genetically detoxified A subunit of the thermolabile toxin from Escherichia coli (LTAK63) adjuvant (rBCG-LTAK63) has previously been shown to confer superior protection and immunogenicity compared to BCG in a murine TB infection model. To further investigate the immunological mechanisms induced by rBCG-LTAK63, we evaluated the immune responses induced by rBCG-LTAK63, BCG, and Mycobacterium tuberculosis (Mtb) H37Rv strains in experimental infections of primary human M1 and M2 macrophages at the transcriptomic and cytokine secretion levels. The rBCG-LTAK63-infected M1 macrophages more profoundly upregulated interferon-inducible genes such as IFIT3, OAS3, and antimicrobial gene CXCL9 compared to BCG, and induced higher levels of inflammatory cytokines such as IL-12(p70), TNF-β, and IL-15. The rBCG-LTAK63-infected M2 macrophages more extensively upregulated transcripts of inflammation-related genes, TAP1, GBP1, SLAMF7, TNIP1, and IL6, and induced higher levels of cytokines related to inflammation and tissue repair, MCP-3 and EGF, as compared to BCG. Thus, our data revealed an important signature of immune responses induced in human macrophages by rBCG-LTAK63 associated with increased inflammation, activation, and tissue repair, which may be correlated with a protective immune response against TB.